Pengaruh Adanya Program Keluarga Harapan Bagi Kesejahteraan Keluarga Penerima Manfaat Program - Fitri Kamilah; Saeful Anwar; Ratna Dewi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The purpose of this study is to determine the level of implementation of the Program Keluarga Harapan, the level of welfare of poor families and how much influence the Program Keluarga Harapan has on the welfare of poor families. The method used is a quantitative method which focuses more on numerical data and uses statistical analysis techniques. The data analysis technique used is a simple linear regression analysis technique with the help of SPSS version 25. This study uses random sampling with 79 respondents from KPM PKH in Cibuntu Village which are divided into 10 RW and from 73 RT. The results showed that there was a significant influence between the Program Keluarga Harapan on the welfare of poor families in Cibuntu Village. Program Keluarga Harapan falls into the category of a fairly strong correlation with a value of 0.527. Furthermore, the coefficient of determination is 0.278, which means that 27.8% of the welfare of poor families in Cibuntu Village is influenced by the Program Keluarga Harapan and the rest is influenced by other factors.